The factor of control of activity circumstances in social adjustment - Suslavičius, A. (Psichologija, 1989)
The problem of the effect of the control of activity circumstances on the social adjustment of the personality is discussed in the report. In experiments both animals and human being were subjected to emotionally aversive stimuli, which could be avoided, and, hence, controlled, or otherwise. Hence, the opposite results have been obtained. The probability of controlling activity circumstances evokes initiative. The lack of the possibility of controlling activity circumstances brings forth the so-called "learned helplessness". The responsibility of the personality for the results of his activity is discussed in the light of the above presented theoretical and ,empirical data; other relevant social problems are also discussed.